2021
DOI: 10.1177/00178969211019459
|View full text |Cite
|
Sign up to set email alerts
|

Children’s pictures of COVID-19 and measures to mitigate its spread: An international qualitative study

Abstract: Objectives: To gain insight into children’s health-related knowledge and understanding of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) and COVID-19, and measures adopted to mitigate transmission. Design: A child-centred qualitative creative element embedded in an online mixed-methods survey of children aged 7–12 years. Setting: Children participated in the study in six countries – the UK, Australia, Sweden, Brazil, Spain and Canada. Method: A qualitative creative component, embedded in an online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Despite the often adult‐centric nature of the public health discourse, participants had a clear sense of what they should be doing in relation to infection control. Similar findings have been reported by Bray et al 26 , 27 However, our study also highlights some of the potential unintended consequences of children's successful uptake of the public health messaging. There was a clear sense of fear expressed by children for their families and friends, with a particular emphasis on death and dying.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite the often adult‐centric nature of the public health discourse, participants had a clear sense of what they should be doing in relation to infection control. Similar findings have been reported by Bray et al 26 , 27 However, our study also highlights some of the potential unintended consequences of children's successful uptake of the public health messaging. There was a clear sense of fear expressed by children for their families and friends, with a particular emphasis on death and dying.…”
Section: Discussionsupporting
confidence: 91%
“…Their social responsibility in relation to their family, school and wider community came through clearly. Such findings have been echoed by Bray et al 26,27 in their international survey of young children's health-related knowledge during the COVID-19 pandemic. Bray et al 27 reported children's strong sense of altruism, highlighting children's willingness to make sacrifices to their own lives to support others.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Such insight would allow the selection and formulation of age-appropriate and accurate explanations and representations that they could meaningfully handle. This, in turn, would make learning about viruses relevant to children and support them in preserving their overall wellbeing (Assante and Candel, 2020;Berasategi et al, 2020;Garcia de Avila et al, 2020;Idoiaga et al, 2020;Majid et al, 2020;Bray et al, 2021b;Manches and Ainsworth, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, despite the previously documented lack of appropriate understanding of infectious diseases and prevention practices in non-experts (Jee et al, 2015), recent studies report high levels of awareness of COVID-19 even in young children (Rydström et al, 2022), and their sensitivity in perceiving and adopting adults' reactions to the pandemic (Valadez et al, 2020;Thompson et al, 2021). This awareness has been revealed in children's ability to distinguish SARS-CoV-2 (cause) from ; to name common symptoms of the disease (for instance cough, fever, or sneeze); to understand the possibility of asymptomatic infection; to recognize the necessity of preventive and mitigation practices such as social distancing or handwashing; to describe airborne transmission and high contagiousness of the virus (Idoiaga et al, 2020;Bray et al, 2021b;Christidou et al, 2021;Martinerie et al, 2021;Thompson et al, 2021;Bonoti et al, 2022;Maftei et al, 2022;Rydström et al, 2022).…”
Section: Introductionmentioning
confidence: 99%